2012
DOI: 10.1097/ijg.0b013e31821dac86
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Medication Adherence to Topical Glaucoma Therapy

Abstract: Introduction/Purpose To determine the associations between medical, demographic, socioeconomic, and ocular factors and adherence to topical glaucoma ocular hypotensive therapy. Methods One-hundred and sixteen patients with ocular hypertension or open angle glaucoma from two tertiary glaucoma services participated in this prospective study. Adherence to ocular hypotensive therapy was measured using an electronic dose monitor (Travatan Dosing Aid, Alcon Laboratories Inc., Fort Worth, TX) and collected data at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 47 publications
(43 reference statements)
4
93
0
3
Order By: Relevance
“…39 It is unfortunate that more reliable clinical outcome measures could not be used, but within the time scale and number of follow-up visits, it is unlikely that changes in the visual field or optic nerve head would reach significance. IOP recordings taken at clinic visits are known to be unreliable at predicting adherence as some patients pay more attention to medication taking immediately before and after clinic appointments; 16,43 however, as both IOP fluctuation and changes in clinical management correlated well with refill and self-report adherence, the authors believe their inclusion was justified for the time period available.…”
Section: Discussionmentioning
confidence: 99%
“…39 It is unfortunate that more reliable clinical outcome measures could not be used, but within the time scale and number of follow-up visits, it is unlikely that changes in the visual field or optic nerve head would reach significance. IOP recordings taken at clinic visits are known to be unreliable at predicting adherence as some patients pay more attention to medication taking immediately before and after clinic appointments; 16,43 however, as both IOP fluctuation and changes in clinical management correlated well with refill and self-report adherence, the authors believe their inclusion was justified for the time period available.…”
Section: Discussionmentioning
confidence: 99%
“…10 To increase compliance in glaucoma patients, approaches like electronic dosing aids, motivational-and patientcentered communication strategies, and video documentation are being used, but so far the results have been mixed. 15,17,[19][20][21][22] A study examining patient compliance for 3 months after providing an electronic dosing aid showed 96% adherence within the first 10 days; this decreased slightly to 86% compliance for the remainder of the study. 19 In a similar study, Dreer et al 20 found that when using an electronic dosing aid 80% of patients took some amount of drops within 6 hours of their prescribed dosing time, but only 64% took the prescribed amount of drops within 3 hours of the prescribed dosing time.…”
Section: Discussionmentioning
confidence: 99%
“…15,17,[19][20][21][22] A study examining patient compliance for 3 months after providing an electronic dosing aid showed 96% adherence within the first 10 days; this decreased slightly to 86% compliance for the remainder of the study. 19 In a similar study, Dreer et al 20 found that when using an electronic dosing aid 80% of patients took some amount of drops within 6 hours of their prescribed dosing time, but only 64% took the prescribed amount of drops within 3 hours of the prescribed dosing time. Hermann et al 57 determined adherence in patients aware of electronic monitoring was no different than in patients who were unaware (67.5% compared to 69.5%), while Okeke et al 58 showed 45% of study participants who were provided free medications and were aware they were being monitored took less than 75% of intended doses during the 3 month study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations